Biodiesel oil pool fire under air crossflow conditions: Burning rate, flame geometric parameters and temperatures. (March 2020) - Salvagni, Rafael Gialdi; Indrusiak, Maria Luiza Sperb; Centeno, Felipe Roman
Highlights: Experiments were performed in small biodiesel pool fires in a wind tunnel. Air crossflow velocities ranged from 0.0 m/s (quiescent air) to 4.0 m/s. Parameters evaluated: mass burning rates, flame geometry and IR-measured temperatures. Flame lengths and tilt angles were compared to existing correlations. Biodiesel fires presented longer flames and higher temperatures than diesel fires. Abstract: The replacement of fossil fuels with renewable ones is an irreversible worldwide trend. More specifically, biodiesel made either from animal fat residue or vegetable oil is being increasingly used. Biodiesel storage tanks are as prone to hazardous fires as other fuel tanks. In this article we present the results of an experimental investigation of biodiesel B100 pool fires in reduced scale submitted to an air crossflow. Regular and infrared images were used to obtain flame geometric parameters and temperature fields for conditions ranging from quiescent air to crossflow velocities of up to 4.0 m/s. Mass burning rates were also obtained for the same air flow conditions. Results were compared with a previous study of regular diesel pool fires conducted with the same experimental apparatus and correlations from literature. It was shown that, compared to diesel fires, biodiesel fires presented longer flames and higher temperatures both in the flame and plume regions as well as downstream of the pool. This indicates that biodiesel storage devices are likely more prone to dangerous fire events than diesel ones.